[PP.16.03] IS TRANSIENT RECEPTOR POTENTIAL VANILLOID TYPE 1 (TRPV1) A NEW TARGET FOR CARDIOPROTECTION?. (September 2016) - Al-Mawla, R.; Païta, L.; Bidault-Ducreux, S.; Chouabe, C.; Durand, A.; Augeul, L.; Dupré-Aucouturier, S.; Bonvallet, R.; Ovize, M.; Van Coppenolle, F.
Abstract : Objective: Nowadays, cardiac arrest is a major cause of mortality in industrial countries. In France 120 000 persons are touched every year. Recently, it has been shown that isoflurane allows at the same time a pre- and a post-conditioning of the heart under experimental and clinical ischemic conditions in order to decrease infarct size (Landoni et al., 2013). Design and method: In the context of infarct, intracellular calcium overload is known to be one of the aggravating factors of ischemic injuries. Generally, isoflurane appears to modulate intracellular calcium content (Tampo et al., 2009). Calcium homeostasis is regulated by several Ca2+ pumps and channels located at the sarcolemma or at the reticulum membrane. Among them, we find calcium passive leak channels, such as TRPV1. In skeletal muscle, we recently demonstrated that TRPV1 is located in the longitudinal part of the SR and respond to pharmacological and physiological activations (Lotteau et al., 2013). We have also evidenced that TRPV1 is a potential target of isoflurane (unpublished data). Our hypothesis is that TRPV1 could similarly be one of the isoflurane targets in cardiac muscle. Results: Biochemical analysis and intracellular Ca2+ measurements were performed on cardiomyocytes from wild-type and TRPV1-KO mice. Our in vitro results show that: (i) TRPV1 is expressed in cardiac cells; (ii) an increase in intracellular calcium concentration ([Ca2+]i) is elicited under TRPV1 activation; (iii) TRPV1 could be a direct target of isoflurane. In parallel, our in vivo results indicate that a pharmacological preconditioning by isoflurane decrease the infarct size, probably though activation of TRPV1. Conclusions: According to the fact that TRPV1 activity can be modulated by a lot of pharmacological molecules and volatile anesthetics, this channel may serve as therapeutic target to reduce the infarct size.